Optimalisasi Mutu Pendidikan di KB PAUD Terpadu Al Bahjah melalui Peningkatan Kompetensi Guru Berbasis Forum Group Discussion - Carnawi, Carnawi; Zamzami, Zamzami; Abdullah, Imam; Gunawan, Gunawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aimed to optimize the quality of education at KB PAUD Terpadu Al-Bahjah by enhancing teacher competence through a Forum Group Discussion (FGD) approach. The method involved initial observation, material preparation, interactive FGDs, and post-activity evaluation. The results revealed an improvement in teachers’ understanding of classroom management, curriculum planning, and the implementation of creative strategies based on group discussion. Scientific findings indicate that FGDs promote collaboration, critical reflection, and the sharing of best practices among educators, significantly contributing to professional development. This aligns with collaborative learning theories emphasizing social interaction as a means of competency improvement. The program created a positive impact by fostering new skills and a collaborative work culture that supports improved educational quality in early childhood institutions.